A systematic review and meta-analysis examining the effects of cannabis and its derivatives in adults with malignant CNS tumors. Issue 4 (3rd April 2020) - Rodriguez-Almaraz, Jesus-Eduardo; Chang, Susan; Clarke, Jennifer; Oberheim-Bush, Nancy Ann; Taylor, Jennie; Buerki, Robin; Berger, Mitchel; Zablotska, Lydia; Lobach, Iryna; Butowski, Nicholas
Abstract: Background: Primary CNS tumors constitute a heterogeneous group of neoplasms that share a considerable morbidity and mortality rate. To help control tumor growth and clinical outcomes (overall survival, progression-free survival, quality of life) symptoms, patients often resort to alternative therapies, including the use of cannabis. Despite rapidly growing popularity, cannabis and its impact on patients with primary malignant CNS tumors is understudied. Methods: To shed light on the lack of scientific evidence in this field, in November 2018 we conducted a search and examination of cannabis in neuro-oncology in major journal databases and bibliographies of selected articles, and through abstracts of annual meetings using prespecified criteria in line with the Cochrane Collaboration guidelines. Results: We identified 45 publications, of which 9 were selected. Five studies were included. Publication dates ranged from 2004 to 2018 and included varying histologies of primary brain tumors. The average survival at 1 year was 56.09% (95% CI: 48.28-63.9). There was no difference in risk ratio (RR) for death at 1 year between groups (RR: 1.069 [95% CI: 0.139-8.25]). We found strong evidence of heterogeneity (Q = 74.0%; P  = .021). We found no statistical evidence of publication bias ( P  = .117; SD = 1.91). Conclusions: There was limited moderate-quality evidence that supports the use of cannabinoids as adjuvant to the standard of care in the treatment of brain and CNS tumors. There was very low-quality evidence suggesting that cannabinoids were associated with adult-onset gliomas. Further prospective clinical trials are necessary to adequately evaluate the impact of cannabinoids on CNS tumors, specifically on survival and quality of life.